Estimating bat diversity in forests: Implications of sonotype-based acoustic classification - Riccardo Fornaro; Francesco Giannino; Mirjam Knörnschild; Danilo Russo (Forest Ecology and Management, 2026)

On the move: southern range expansion of Italian parti-coloured bats - Emiliano Mori; Leonardo Ancillotto; Mattia Falaschi; Orly Razgour; Mariella Baratti; Gianna Dondini; Simone Vergari; Andrea Viviano; Ivana Budinski; Marcello Consolo; Penelope Fialas; Renato Pontarini; et al. (Mammalian Biology, 2026)

Context-dependent responses of bats to artificial light at night in urban and natural woodlands - Vincenzo Meola; Belma Šestović; Danilo Russo (Science of The Total Environment, 2026)

Dog–wildlife interactions across Spain suggest vulnerability in periurban areas and aquatic ecosystems - Lorenzo Lazzeri; Álvaro Luna; Emiliano Mori; Danilo Russo; Sandro Lovari; Maia Pastres; Leonardo Ancillotto; Davide Sogliani (European Journal of Wildlife Research, 2026)

Integrated design, scale-up, and surrogate-based optimization of PSA systems for hydrogen purification from ammonia decomposition - Bahare Abdoos; Almerinda Di Benedetto; Danilo Russo (Chemical Engineering Journal, 2025)

Spatial proximity to farmland enhances bat richness and activity in planted forests - Claudia Allegrini; Vincenzo Meola; Danilo Russo; Boris Krasnov; Carmi Korine (Agriculture, Ecosystems & Environment, 2025)

Riparian forest paves the way to climate-driven expansion in bats: Evidence from a fine-scale elevational shift - Chiara Belli; Luca Cistrone; Belma Sestovic; Ioannis Ekklisiarchos; Miren Aldasoro; Chiara Borgonovo; Ilaria Migliaresi; Mariella Di Domenico; John Ratcliffe; Danilo Russo (Forest Ecology and Management, 2025)

The italian national genomic strategy: current status, challenges, and future perspectives in clinical practice and public health - Francesco Andrea Causio; Sara Farina; Alessandra Maio; Flavia Beccia; Luigi Russo; Valentina Baccolini; Matteo Chiara; Americo Cicchetti; Gualtiero I. Colombo; Giovanni Comandé; Domenico Coviello; Ruggero De Maria; et al. (Journal of Community Genetics, 2025)
This article presents the outcomes of a national initiative aimed at developing a technical document to support the future Italian National Genomic Strategy, carried out from 2021 to 2024 through the collaboration of 14 research institutions. The project was designed to align with major European genomic initiatives, particularly the “1 + Million Genomes” (1 + MG) Declaration and its supporting programs, including Beyond 1 Million Genomes (B1 + MG), the Genomic Data Infrastructure (GDI), and Genome of Europe (GoE). The initiative was structured around 12 National Mirror Groups (NMGs), each addressing a specific domain such as clinical implementation, ethical and legal issues, data governance, health economics, and public engagement. Through expert consensus and coordinated activities, the project produced a comprehensive technical document outlining seven strategic lines and related intervention areas. These include the integration of genomic testing into clinical practice, development of specialized genomic centers, creation of a national genomic data infrastructure, professional training, and public education. The proposed strategy emphasizes equitable access to genomic medicine, the use of health technology assessment to evaluate new technologies, and the importance of citizen engagement and literacy. By fostering collaboration among institutions, healthcare professionals, and the public, the final goal is to position Italy as a leader in genomic medicine and ensure the responsible, effective, and ethical use of genomics in public health and clinical care.

Social vocalizations show stronger phylogenetic conservatism than echolocation calls in closely related pipistrelle bats - Danilo Russo; Martina Nagy; Iva Visnakova; Beatrix Wuntke; Guido Pfalzer; Panagiotis Georgiakakis; Mirjam Knörnschild (Animal Behaviour, 2025)

Ground cover promotes enhanced bat activity in high-value insular vineyards - Luca Cistrone; Henry Schofield; Danilo Russo (Agriculture, Ecosystems & Environment, 2025)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

Corrigendum to “Susceptibility of bats to ecological and evolutionary traps” [Biol. Conserv. 305 (2025) 111110] - Krizler C. Tanalgo; Kier C. Dela Cruz; Danilo Russo (Biological Conservation, 2025)

Taxonomy for conservation: multi-taxa survey evidences a biodiversity hotspot in the Central Apennines (Salto-Cicolano District) - Pierangelo Crucitti; Danilo Russo; Giovanni Amori; Marcello Vitale; Corrado Battisti; Roberto Antonelli; Davide Brocchieri; Marco Giardini; Luigi Lenzini; Paolo Mazzei; Nicolò Pellecchia; Luca Tringali; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Susceptibility of bats to ecological and evolutionary traps - Krizler C. Tanalgo; Kier C. Dela Cruz; Danilo Russo (Biological Conservation, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Unlocking glycerol Potential: Novel pathway for hydrogen production and Value-Added chemicals - Alessandra Di Nardo; Gianluca Landi; Giuseppina Luciani; Maria Portarapillo; Giovanna Ruoppolo; Danilo Russo; Armando Zarrelli; Almerinda Di Benedetto (Chemical Engineering Journal, 2024)

To improve or not to improve? The dilemma of “bat-friendly” farmland potentially becoming an ecological trap - Danilo Russo; Krizler Tanalgo; Hugo Rebelo; Luca Cistrone (Agriculture, Ecosystems & Environment, 2024)

Of greater noctule “migration” from Russia to Italy: a comment on Vasenkov et al. (2023) - Danilo Russo; Anne Mäenurm; Adriano Martinoli; Luca Cistrone (Mammalian Biology, 2024)
We comment on a recent study (Vasenkov et al. in Dokl Biol Sci 513:395–399, 2023, https://doi.org/10.1134/S0012496623700746 ) presenting the movement paths of three greater noctule bats ( Nyctalus lasiopterus ), two juveniles and an adult, tracked from Russia in September–October 2020 and 2021, with particular emphasis on the unprecedented straight-line migration of a juvenile male to Italy. Notably, the juvenile's extraordinary 2515 km migration marks the longest recorded (as the crow flies) movement in a bat species. We argue that the two juveniles may represent cases of dispersal. Despite the attention garnered by Vasenkov et al . ’s findings, caution is warranted in interpreting the broader migration picture. The paper’s dissemination underscores a potential oversimplification, neglecting key insights from recent work conducted in Italy that documented the year-round presence, hibernation, and parturition of N. lasiopterus in an area of the Friuli Venezia-Giulia region where the juvenile male tracked from Russia stopped over. Besides, inferring the existence of migratory routes based on small numbers of tracked bats is insufficient. The oversight of these findings may imply a misleading narrative about the species' behaviour, likely representing a case of partial migration, a pattern widespread among migratory bat species.

Cryptic hybridization between the ancient lineages of Natterer's bat ( Myotis nattereri ) - Darija Josić; Emrah Çoraman; Isabelle Waurick; Sören Franzenburg; Leonardo Ancillotto; Branka Bajić; Ivana Budinski; Christian Dietz; Tamás Görföl; Sofia I. Hayden Bofill; Primož Presetnik; Danilo Russo; et al. (Molecular Ecology, 2024)
Studying hybrid zones that form between morphologically cryptic taxa offers valuable insights into the mechanisms of cryptic speciation and the evolution of reproductive barriers. Although hybrid zones have long been the focus of evolutionary studies, the awareness of cryptic hybrid zones increased recently due to rapidly growing evidence of biological diversity lacking obvious phenotypic differentiation. The characterization of cryptic hybrid zones with genome‐wide analysis is in its early stages and offers new perspectives for studying population admixture and thus the impact of gene flow. In this study, we investigate the population genomics of the Myotis nattereri complex in one of its secondary contact zones, where a putative hybrid zone is formed between two of its cryptic lineages. By utilizing a whole‐genome shotgun sequencing approach, we aim to characterize this cryptic hybrid zone in detail. Demographic analysis suggests that the cryptic lineages diverged during the Pliocene, c. 3.6 million years ago. Despite this ancient separation, the populations in the contact zone exhibit mitochondrial introgression and a considerable amount of mixing in nuclear genomes. The genomic structure of the populations corresponds to geographic locations and the genomic admixture changes along a geographic gradient. These findings suggest that there is no effective hybridization barrier between both lineages, nevertheless, their population structure is shaped by dispersal barriers. Our findings highlight how such deeply diverged cryptic lineages can still readily hybridize in secondary contact.

A bat a day keeps the pest away: Bats provide valuable protection from pests in organic apple orchards - Leonardo Ancillotto; Massimiliano Borrello; Francesco Caracciolo; Fabio Dartora; Michela Ruberto; Rosario Rummo; Chiara Scaramella; Arturo Odore; Antonio Pietro Garonna; Danilo Russo (Journal for Nature Conservation, 2024)

Higher and bigger: How riparian bats react to climate change - Danilo Russo; Gareth Jones; Marta Polizzi; Vincenzo Meola; Luca Cistrone (Science of The Total Environment, 2024)

Citizen science and diet analysis shed light on dog-wildlife interactions in Italy - Davide Sogliani; Emiliano Mori; Sandro Lovari; Lorenzo Lazzeri; Alice Longoni; Karol Tabarelli De Fatis; Patrizia Sabatini; Matteo Riccardo Di Nicola; Danilo Russo (Biodiversity and Conservation, 2023)
Domestic dogs Canis familiaris may cause a range of impacts on wildlife through predation, competition, pathogen transmission, harassment and hybridisation with wolves and other wild canids, yet such effects are less known than those of other domestic species. In this work, we have combined citizen science data and information collected by scientists on the potential impact of free-ranging dogs on wildlife in Italy. Citizen science data, obtained through online surveys on social networks, consisted of pictures of wildlife killed or harassed by dogs from 2002 to 2022. Additional records were collected from articles in newspapers. We also provide the results of a diet analysis from domestic dog scats, collected in the countryside in central Italy in 1998–1999, for which we assessed prey selection by comparing consumption with availability. The citizen science survey provided 589 records: dogs attacked and killed 95 species, mostly mammals and birds, including small game species. Among species of conservation concern, dogs attacked/killed Mustela putorius and Hystrix cristata , both included in Annex IV of the Habitats Directive, and the Italian endemic Lepus corsicanus and Passer italiae . Over 90% of the attacks were caused by unleashed dogs in the presence of their owner in urban and periurban areas. The 148 dog scats analysed contained 30 prey species, mainly mammals, which made the staple of the dog diet, followed by amorphous material, most likely pet food. Remains of domestic sheep were frequent in the diet, as were hares Lepus europaeus and roe deer Capreolus capreolus among wild mammals. Wild boar Sus scrofa ranked first among the selected prey species, followed by hares, whereas roe deer and grey partridges Perdix perdix were negatively selected. The mitigation of the impact of domestic carnivores on wildlife strongly requires awareness raising to promote responsible pet ownership and strict avoidance of dogs’ free-ranging behaviour, especially where encounters with wildlife are most likely.

Forest islands in farmland provide vital roost trees year-round for giant and common noctule bats: Management implications - Danilo Russo; Anne Mäenurm; Adriano Martinoli; Maurizio Zotti; Luca Cistrone (Forest Ecology and Management, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Predator-prey traits and foraging habitat shape the diet of a common insectivorous bat - Leonardo Ancillotto; Angelica Falanga; Giulia Agostinetto; Nicola Tommasi; Antonio P. Garonna; Flavia de Benedetta; Umberto Bernardo; Andrea Galimberti; Paola Conti; Danilo Russo (Acta Oecologica, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Organic farming sustains bats in Mediterranean farmland - Leonardo Ancillotto; Chiara Scaramella; Fabio Dartora; Antonello Migliozzi; Danilo Russo (Agriculture, Ecosystems & Environment, 2023)

The rise and fall of an alien: why the successful colonizer Littorina saxatilis failed to invade the Mediterranean Sea - Luciano Bosso; Sonia Smeraldo; Danilo Russo; Maria Luisa Chiusano; Giorgio Bertorelle; Kerstin Johannesson; Roger K. Butlin; Roberto Danovaro; Francesca Raffini (Biological Invasions, 2022)

Bat selfies: photographic surveys of flying bats - Jens Rydell; Danilo Russo; Price Sewell; Ernest C. J. Seamark; Charles M. Francis; Sherri L. Fenton; M. Brock Fenton (Mammalian Biology, 2022)
The recent pandemic and other environmental concerns have resulted in restrictions on research and surveys involving capture and handling bats. While acoustic surveys have been widely used as an alternative survey method, in this study, we show how photographic surveys can offer an important contribution to study and survey bats. We outline approaches, using high speed flash and automated trip beams to obtain photos of flying bats of sufficient quality for reliable identification of species. We show, through a series of examples of setups and photographs, that photography is effective for surveying bats at a variety of sites, where bats roost, drink, and forage. We note, however, that photographic surveys cannot replace capture in all situations. In addition, although photographing bats is less invasive than capturing them, it can involve disturbance, so we stress the importance of minimizing the impact of such operations on bats.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Body size of Italian greater horseshoe bats (Rhinolophus ferrumequinum) increased over one century and a half: a response to climate change? - Valeria B. Salinas-Ramos; Paolo Agnelli; Luciano Bosso; Leonardo Ancillotto; Danilo Russo (Mammalian Biology, 2021)

Adverse effects of noise pollution on foraging and drinking behaviour of insectivorous desert bats - Adi Domer; Carmi Korine; Mallory Slack; Indira Rojas; Daniela Mathieu; Aaron Mayo; Danilo Russo (Mammalian Biology, 2021)

Global patterns of functional trait variation along aridity gradients in bats - Irene Conenna; Luca Santini; Ricardo Rocha; Ara Monadjem; Mar Cabeza; Danilo Russo (Global Ecology and Biogeography, 2021)
Aim Our understanding of the biological strategies employed by species to cope with challenges posed by aridity is still limited. Despite being sensitive to water loss, bats successfully inhabit a wide range of arid lands. We here investigated how functional traits of bat assemblages vary along the global aridity gradient to identify traits that favour their persistence in arid environments. Location Global. Time period Contemporary. Major taxa studied Bats. Methods We mapped the assemblage‐level averages of four key bat traits describing wing morphology, echolocation and body size, based on a grid of 100‐km resolution and a pool of 915 bat species, and modelled them against aridity values. To support our results, we conducted analyses also at the species level to control for phylogenetic autocorrelation. Results At the assemblage level, we detected a rise in values of aspect ratio, wing loading and forearm length, and a decrease in echolocation frequency with increasing aridity. These patterns were consistent with trends detected at the species level for all traits. Main conclusions Our findings show that trait variation in bats is associated with the aridity gradient and suggest that greater mobility and larger body size are advantageous features in arid environments. Greater mobility favours bats’ ability to track patchy and temporary resources, while the reduced surface‐to‐volume ratio associated with a larger body size is likely to reduce water stress by limiting cutaneous evaporation. These findings highlight the importance of extending attention from species‐specific adaptations to broad scale and multispecies variation in traits when investigating the ability of species to withstand arid conditions.

Modelling risks posed by wind turbines and power lines to soaring birds: the black stork (Ciconia nigra) in Italy as a case study - Sonia Smeraldo; Luciano Bosso; Maurizio Fraissinet; Lucio Bordignon; Massimo Brunelli; Leonardo Ancillotto; Danilo Russo (Biodiversity and Conservation, 2020)

3D Photogrammetry of Bat Skulls: Perspectives for Macro-evolutionary Analyses - Giada Giacomini; Dino Scaravelli; Anthony Herrel; Alessio Veneziano; Danilo Russo; Richard P. Brown; Carlo Meloro (Evolutionary Biology, 2019)

One strategy does not fit all: determinants of urban adaptation in mammals - Luca Santini; Manuela González‐Suárez; Danilo Russo; Alejandro Gonzalez‐Voyer; Achaz von Hardenberg; Leonardo Ancillotto (Ecology Letters, 2019)
Urbanisation exposes wildlife to new challenging conditions and environmental pressures. Some mammalian species have adapted to these novel environments, but it remains unclear which characteristics allow them to persist. To address this question, we identified 190 mammals regularly recorded in urban settlements worldwide, and used phylogenetic path analysis to test hypotheses regarding which behavioural, ecological and life history traits favour adaptation to urban environments for different mammalian groups. Our results show that all urban mammals produce larger litters; whereas other traits such as body size, behavioural plasticity and diet diversity were important for some but not all taxonomic groups. This variation highlights the idiosyncrasies of the urban adaptation process and likely reflects the diversity of ecological niches and roles mammals can play. Our study contributes towards a better understanding of mammal association to humans, which will ultimately allow the design of wildlife‐friendly urban environments and contribute to mitigate human‐wildlife conflicts.

Ignoring seasonal changes in the ecological niche of non-migratory species may lead to biases in potential distribution models: lessons from bats - Sonia Smeraldo; Mirko Di Febbraro; Luciano Bosso; Carles Flaquer; David Guixé; Fulgencio Lisón; Angelika Meschede; Javier Juste; Julia Prüger; Xavier Puig-Montserrat; Danilo Russo (Biodiversity and Conservation, 2018)

Assessment of Detection Methods and Vegetation Associations for Introduced Finlayson’s Squirrels (Callosciurus finlaysonii) in Italy - Leonardo Ancillotto; Tommaso Notomista; Emiliano Mori; Sandro Bertolino; Danilo Russo (Environmental Management, 2018)

Agriculture shapes the trophic niche of a bat preying on multiple pest arthropods across Europe: Evidence from DNA metabarcoding - Ostaizka Aizpurua; Ivana Budinski; Panagiotis Georgiakakis; Shyam Gopalakrishnan; Carlos Ibañez; Vanessa Mata; Hugo Rebelo; Danilo Russo; Farkas Szodoray‐Parádi; Violeta Zhelyazkova; Vida Zrncic; M. Thomas P. Gilbert; et al. (Molecular Ecology, 2018)
The interaction between agricultural production and wildlife can shape, and even condition, the functioning of both systems. In this study, we i) explored the degree to which a widespread European bat, namely the common bent‐wing bat Miniopterus schreibersii, consumes crop‐damaging insects at a continental scale, and ii) tested whether its dietary niche is shaped by the extension and type of agricultural fields. We employed a dual‐primer DNA metabarcoding approach to characterize arthropod 16S and COI DNA sequences within bat faecal pellets collected across 16 Southern European localities, to first characterize the bat species’ dietary niche, second measure the incidence of agricultural pests across their ranges and third assess whether geographical dietary variation responds to climatic, landscape diversity, agriculture type and vegetation productivity factors. We detected 12 arthropod orders, among which lepidopterans were predominant. We identified >200 species, 44 of which are known to cause agricultural damage. Pest species were detected at all but one sampling site and in 94% of the analysed samples. Furthermore, the dietary diversity of M. schreibersii exhibited a negative linear relation with the area of intensive agricultural fields, thus suggesting crops restrict the dietary niche of bats to prey taxa associated with agricultural production within their foraging range. Overall, our results imply that M. schreibersii might be a valuable asset for biological pest suppression in a variety of agricultural productions and highlight the dynamic interplay between wildlife and agricultural systems.

Does the jack of all trades fare best? Survival and niche width in Late Pleistocene megafauna - Mirko Di Febbraro; Francesco Carotenuto; Silvia Castiglione; Danilo Russo; Anna Loy; Luigi Maiorano; Pasquale Raia (Journal of Biogeography, 2017)
Aim We sought to assess different megafaunal species responses to the intense climatic changes that characterized the end of the Quaternary. Location Eurasia. Methods We used species distribution modelling, niche overlap tests and co‐occurrence analysis to model climatic niche evolution and change in six different megafauna species, including three extinct (woolly mammoth, woolly rhino and steppe bison) and three extant (red deer, wolf and reindeer) species. Results Co‐occurrence analysis indicates mammoth, rhino, reindeer and steppe bison to be significantly associated to each other in the fossil record in cold, arid environments. In contrast, red deer and wolf show no evidence for strong habitat requirements, although they both tended to be associated with more humid conditions than the other megafauna. Woolly mammoth and the woolly rhino were the best adapted to the cold, arid conditions dominating the Eurasian landscapes during the Last Glacial Maximum ( LGM ). Extant species did not exhibit larger climatic niches than extinct species, but changed more from one period to the next than those of extinct species. Main conclusions Although they did not have wider climatic niches, and were the least adapted to cold climates, red deer and the wolf were able to withstand the harsh climatic conditions of the LGM . Conversely, the now extinct mammoth and woolly rhino did not survive the demise of the LGM environment. Although “cold‐adapted”, reindeer survived the LGM by occupying a northerly distribution similar to today. Independent evidence indicates the steppe bison lineage might have survived in North America. Our data are consistent with a strong climatic control on the fate of late Quaternary megafauna species in Eurasia. We were unable to exclude a sizeable effect of human intervention by overhunting.

Extinctions of introduced game species on oceanic islands: curse for hunters or conservation opportunities? - Ricardo Rocha; Miguel M. Sequeira; Leo R. Douglas; Manuela Gouveia; Roberto Jardim; José Jesus; Holly P. Jones; Danilo Russo (Biodiversity and Conservation, 2017)

Modelling the Risk Posed by the Zebra Mussel Dreissena polymorpha: Italy as a Case Study - Luciano Bosso; Carmelina De Conno; Danilo Russo (Environmental Management, 2017)

Sacrificial photocatalysis: removal of nitrate and hydrogen production by nano-copper-loaded P25 titania. A kinetic and ecotoxicological assessment - Roberta Lucchetti; Antonietta Siciliano; Laura Clarizia; Danilo Russo; Ilaria Di Somma; Francesco Di Natale; Marco Guida; Roberto Andreozzi; Raffaele Marotta (Environmental Science and Pollution Research, 2017)

Shedding light on the effects of climate change on the potential distribution of Xylella fastidiosa in the Mediterranean basin - Luciano Bosso; Mirko Di Febbraro; Gennaro Cristinzio; Astolfo Zoina; Danilo Russo (Biological Invasions, 2016)

Cranial size has increased over 133 years in a common bat, Pipistrellus kuhlii : a response to changing climate or urbanization? - Alessandra Tomassini; Paolo Colangelo; Paolo Agnelli; Gareth Jones; Danilo Russo (Journal of Biogeography, 2014)
Aim Bats are promising candidates for studying morphometric responses to anthropogenic climate or land‐use changes. We assessed whether the cranial size of a common bat ( P ipistrellus kuhlii ) had changed between 1875 and 2007. We formulated the following hypotheses: (1) if heat loss is an important reaction to climate change, body size will have decreased in response to the increased temperatures, because small bats have a larger surface‐to‐volume ratio and dissipate heat more effectively; (2) if water loss is the main driver, body size will have increased in response to the temperature increase, because larger bats will lose water more slowly through a reduced surface‐to‐volume ratio; (3) the energetic benefits provided by urbanization (food concentration at street lamps, warmer maternity roosts in buildings) will lead to a general body size increase in P . kuhlii ; and (4) because street lamps impair moth antipredatory manoeuvres, cranial size may have selectively increased as an adaptive response to handle larger prey (moths) in artificially illuminated sites. Ours is the first study to assess temporal trends in bat body size over more than a century and to relate them to urbanization. Location Mainland I taly. Methods We used traditional morphometrics to compare seven variables of skull size in 117 museum specimens (75 female, 42 male). Results Cranial size increased after 1950, but this change was not paralleled by an increase in body size, measured as forearm length. This selective increase matched a rapid increase in electric public illumination in I taly. Main conclusions Street lights are crucial foraging sites for P . kuhlii . The directional change that we found in cranial size might represent microevolutionary adaptive tracking of a sudden shift in food size, making more profitable prey available.

Selective aggressiveness in European free-tailed bats (Tadarida teniotis): influence of familiarity, age and sex - Leonardo Ancillotto; Danilo Russo (The Science of Nature, 2014)

Spotting the right spot: computer-aided individual identification of the threatened cerambycid beetle Rosalia alpina - Giovanni Caci; Alessandro Bruno Biscaccianti; Luca Cistrone; Luciano Bosso; Antonio Pietro Garonna; Danilo Russo (Journal of Insect Conservation, 2013)

Phylogeography and postglacial recolonization of Europe by Rhinolophus hipposideros : evidence from multiple genetic markers - Serena E. Dool; Sébastien J. Puechmaille; Christian Dietz; Javier Juste; Carlos Ibáñez; Pavel Hulva; Stéphane G. Roué; Eric J. Petit; Gareth Jones; Danilo Russo; Roberto Toffoli; Andrea Viglino; et al. (Molecular Ecology, 2013)
The demographic history of Rhinolophus hipposideros (lesser horseshoe bat) was reconstructed across its European, North African and Middle‐Eastern distribution prior to, during and following the most recent glaciations by generating and analysing a multimarker data set. This data set consisted of an X‐linked nuclear intron (Bgn; 543 bp), mitochondrial DNA (cytb‐ tRNA ‐control region; 1630 bp) and eight variable microsatellite loci for up to 373 individuals from 86 localities. Using this data set of diverse markers, it was possible to determine the species’ demography at three temporal stages. Nuclear intron data revealed early colonization into Europe from the east, which pre‐dates the Quaternary glaciations. The mtDNA data supported multiple glacial refugia across the Mediterranean, the largest of which were found in the Ibero‐Maghreb region and an eastern location (Anatolia/Middle East)–that were used by R. hipposideros during the most recent glacial cycles. Finally, microsatellites provided the most recent information on these species’ movements since the Last Glacial Maximum and suggested that lineages that had diverged into glacial refugia, such as in the Ibero‐Maghreb region, have remained isolated. These findings should be used to inform future conservation management strategies for R. hipposideros and show the power of using a multimarker data set for phylogeographic studies.

Postglacial colonization of Europe by the barbastelle bat: agreement between molecular data and past predictive modelling - HUGO REBELO; ELSA FROUFE; JOSÉ C. BRITO; DANILO RUSSO; LUCA CISTRONE; NUNO FERRAND; GARETH JONES (Molecular Ecology, 2012)
The barbastelle ( Barbastella barbastellus ) is a rare forest bat with a wide distribution in Europe. Here, we combine results from the analysis of two mtDNA fragments with species distribution modelling to determine glacial refugia and postglacial colonization routes. We also investigated whether niche conservatism occurs in this species. Glacial refugia were identified in the three southern European peninsulas: Iberia, Italy and the Balkans. These latter two refugia played a major role in the postglacial colonization process, with their populations expanding to England and central Europe, respectively. Palaeo‐distribution models predicted that suitable climatic conditions existed in the inferred refugia during the last glacial maximum (LGM). Nevertheless, the overlap between the current and the LGM distributions was almost inexistent in Italy and in the Balkans, meaning that B. barbastellus populations were forced to shift range between glacial and interglacial periods, a process that probably caused some local extinctions. In contrast, Iberian populations showed a ‘refugia within refugium’ pattern, with two unconnected areas containing stable populations (populations that subsisted during both glacial and interglacial phases). Moreover, the match between LGM models and the refugial areas determined by molecular analysis supported the hypothesis of niche conservatism in B. barbastellus . We argue that geographic patterns of genetic structuring, altogether with the modelling results, indicate the existence of four management units for conservation: Morocco, Iberia, Italy and UK, and Balkans and central Europe. In addition, all countries sampled possessed unique gene pools, thus stressing the need for the conservation of local populations.

Habitat selection by the highly endangered long-horned beetle Rosalia alpina in Southern Europe: a multiple spatial scale assessment - Danilo Russo; Luca Cistrone; Antonio P. Garonna (Journal of Insect Conservation, 2011)

Reconsidering the importance of harvested forests for the conservation of tree-dwelling bats - Danilo Russo; Luca Cistrone; Antonio P. Garonna; Gareth Jones (Biodiversity and Conservation, 2010)

Social calls are subject to stabilizing selection in insular bats - Danilo Russo; Sérgio Teixeira; Luca Cistrone; José Jesus; David Teixeira; Tamira Freitas; Gareth Jones (Journal of Biogeography, 2009)
Aim Bats communicate by emitting social calls, and these often elicit reactions in conspecifics. Many such vocalizations are species‐specific so that unambiguous signals can be transmitted and interpreted by conspecifics. In species‐rich assemblages, evolutionary pressures might prompt interspecific diversification of call structure so that communication with heterospecifics is avoided. In species‐poor island communities, where no risk of miscommunication occurs, stabilizing selection should prevail and preserve call structure and function. Call structure in island bats might be inherited from colonizers from the mainland and be maintained with little change in the absence of selection from heterospecifics. To test this hypothesis we studied Pipistrellus maderensis , an insular taxon occurring on the Madeira Archipelago, the Canary Islands and the Azores. It is closely related to one of the most widespread European pipistrelles, Pipistrellus kuhlii . Pipistrellus maderensis most probably evolved from a common ancestor shared with P. kuhlii , or from founders of that taxon that colonized the islands. We hypothesized that on Madeira Island, where no risk of ambiguous communication with heterospecifics exists, the structure and function of social calls should have been preserved by stabilizing selection. Echolocation calls, subject to different selection pressures, may instead show more pronounced differences between P. maderensis and P. kuhlii . Location Madeira Island (Portugal, Atlantic Ocean), central and southern Italy. Methods We recorded social and echolocation calls from allopatric populations of the two pipistrelles and explored interspecific differences in time and frequency characteristics. We also conducted playback experiments by broadcasting recordings of social calls from P. kuhlii and P. maderensis (taken respectively in peninsular Italy and on Madeira) and monitoring the bats’ responses. Results Social call structure showed a strong similarity between species, whereas echolocation calls were markedly different and exhibited a mean divergence of over 6 kHz in their frequency of maximum energy. On Madeira, P. maderensis significantly reduced flight activity when we broadcast P. kuhlii signals, as did P. kuhlii in Italy in response to P. maderensis calls. Main conclusions Reliable interpretation of social calls provides benefits to both the signaller and the receiver because signals help to optimize food exploitation at foraging sites. In the absence of closely related species that can emit similar calls, this advantage may have acted as a strong evolutionary pressure, stabilizing social call structure in P. maderensis in insular ecosystems with limited foraging resources.

Divergent echolocation call frequencies in insular rhinolophids (Chiroptera): a case of character displacement? - Danilo Russo; Mauro Mucedda; Monica Bello; Stefania Biscardi; Ermanno Pidinchedda; Gareth Jones (Journal of Biogeography, 2007)
Aims Because rhinolophids have been hypothesized to use echolocation call frequency to recognize conspecifics, sympatric species calling at similar frequencies should be subject to acoustic character displacement, i.e. a drift in frequency values to minimize the risk of misidentification of conspecifics. However, it has been proposed that insufficient geographical separation between populations in sympatry and allopatry may counter the establishment of frequency differences by character displacement. Here we tested the hypothesis that insular populations should exhibit acoustic divergence, and this should be revealed by comparing call frequencies with those observed in mainland, allopatric populations of conspecifics. We also tested whether the evolutionary pressure towards acoustic divergence should be especially strong at sites where rhinolophid species emitting similar call frequencies roost together in order to minimize interspecific frequency overlap. Location Sardinia and southern Italy (Campania, Lazio, Abruzzo). Methods Time‐expanded echolocation calls and body size were recorded from Sardinian populations of Rhinolophus mehelyi Matschie, Rhinolophus hipposideros (Bechstein) and Rhinolophus euryale Blasius. Both call frequencies and forearm length of insular R. hipposideros and R. euryale were compared with those of populations from mainland areas of Italy where R. mehelyi is absent, to explore the hypothesis that the presence of the latter species (which calls at frequency values intermediate between the other two) may determine acoustic divergence in the other species. For Sardinian R. mehelyi and R. euryale , we also carried out intraspecific comparisons of call frequencies between bats from monospecific colonies and those from mixed colonies. Results As hypothesized, Sardinian R. hipposideros and R. euryale called at frequencies higher and lower, respectively, than in the peninsula. In this way, overlap with R. mehelyi is avoided. Body size showed no difference between insular and peninsular populations, i.e. frequency differences are not a by‐product of difference in body size determined by insularity. Frequency values in Sardinian R. euryale from monospecific colonies did not differ from those of bats roosting together with R. mehelyi . However, R. mehelyi showed frequency values significantly higher when associated with R. euryale , possibly to minimize the risk of species misrecognition. Main conclusions At least under geographical isolation, character displacement may be a causal mechanism for shifts in call frequency of sympatric rhinolophids. Species recognition and facilitation of intraspecific communication (with possible implications for mate recognition) constitute the best candidate factors for the phenomenon we observed.